Non-Destructive Testing (NDT) Method for Defect Detection in Glass Fibre Reinforced Plastic/Polymer (GFRP/GRP) Composite Materials Structures: A Review - Jamil, Jeffry; M. Yusup, Eliza; Osman, Shahrul Azmir (Akademia Baru, 2024)
Various industries are considering metal product in lieu composite materials. Structural engineers appreciate glass fibre reinforced plastic/polymer (GFRP/GRP) because to its high modulus of elasticity, ratio of strength to weight, and corrosion resistance features. It has been discovered that structural engineering defects to be leading cause for the catastrophic consequences. This paper provides an overview of available NDT methods that can be employed to assess the quality of GFRP/GRP composite materials. The most common NDT method used by researchers and practitioners is also discussed, along with the advantages, disadvantages, characteristics, and potential applications of these materials. The review will lead the research using ultrasonic testing as a potential method employing low-frequency transducers with multielement architecture. This study will lead industry players, GFRP/GRP manufacturers, researchers, and NDT practitioners towards the development of technical standards for ultrasonic testing on GFRP/GRP in Malaysia